Interleukin-31 Receptor α Is Required for Basal-Like Breast Cancer Progression - He, Yanling; Zhang, Xinyuan; Pan, Weijun; Tai, Fang; Liang, Li; Shi, Jian (Frontiers in Oncology, 2020)
Purpose: Interleukin-31 receptor α (IL31RA) usually mediates IL-31 induced inflammation and allergic diseases. However, the functional roles of IL-31/IL31RA signaling in basal-like breast cancer (BLBC) progression remain totally unclear. Methods: Tumorsphere formation, transwell and wound healing assays were used to measure the BLBC progression. We implanted tumor cells in mammary fat pad and tail vein of nude mice to detect the growth and metastasis of BLBC cells. Luciferase and ChIP assays were employed to measure the transcriptional regulation. Western blot and real-time PCR assays as well as bio-informatics analyses were conducted to observe the expression of IL31RA. Results: We found that silencing of IL31RA suppresses the cancer stem cell-like properties, migration and invasion of BLBC cells in vitro as well as tumor growth and metastasis in vivo. Knockdown of IL31RA ameliorates IL-31-mediated pro-oncogenic functions. Overexpression of IL31RA in luminal breast cancer cells enhances the cancer stem cell-like properties and cell motility. Our data further identified IL31RA as a target gene of Twist/BRD4 transcription complex. Conclusion: Overall, these data indicate that IL31RA promotes basal-like breast cancer progression and metastasis, suggesting that targeting of IL-31/IL31RA axis might be beneficial to treatment of BLBC.